Rice Grain Storage Reduces Antibiotic Resistance Risks and Pathogens Through Enrichment of Antimicrobial Metabolites - Fang Wu; Yuanpeng Zhang; Peng Huang; Li Li; Yanguang Zhu; Quanxin Rao; Ruizhang Feng; Jie Tu (Journal of Food Quality)
Grain storage is a universal practice critical to food security and economic stability. Although storage conditions and grain quality have been extensively studied, the risks linked to post–market grain storage remain largely overlooked. This study addresses this gap by evaluating the dynamics of potential risk factors, specifically, antibiotic resistance genes (ARGs) and pathogens in rice grains. Metagenomic sequencing of rice grains stored for 1–3 years showed a decline in both ARGs and pathogens with increasing storage duration. Furthermore, it also revealed suppressed horizontal gene transfer mediated via mobile genetic elements, and significant shifts in bacterial community composition. Multiple correlation analyses confirmed the significant reduction of ARGs and pathogens during storage. Integrated transcriptomic and metabolomic analyses identified genes and metabolites with persistent differential expression over the storage period. Notably, genes involved in diterpenoid biosynthesis and metabolites from the luteolin group were consistently upregulated over the 3-year storage period. Moreover, these persistently expressed genes and metabolites showed a strong negative correlation with ARG and pathogen abundance. Consequently, these findings suggest that proper rice grain storage can reduce health risks associated with ARGs and pathogens possibly due to the accumulation of plant-derived antimicrobial compounds during storage.